Recurrent education in the nordic countries (The Nordic Council of Ministers, 1977)
In Scandinavia, recurrent education offers chances for continued periods of work experience and educational experience to equalize educational opportunities between and throughout the generations. In 1975 the Secretariat for Culture set up the Nordic Working Party to consider recurrent education programmes already in existence or being planned. Denmark, Finland, Iceland and Norway were compared as regards school systems, higher education, adult education, labour market issues and vocational education. Problems of information dissemination and finance were discussed. Whilst recurrent education is under discussion little real progress has been made. The planning of adult education, post secondary education, compulsory education and educational leave must be coordinated and complimentary. The Nordic countries are working toward information sharing rather than an overall system